A real-world, cross-sectional, and longitudinal study on high-risk human papillomavirus genotype distribution in 31,942 women in Dongguan, China - Zhong, Huanxia; Pan, Wenwei; Chen, Binbin; Gu, Jiamin; Liang, Yu; Sun, Guoli; Huang, Xinghua; Yuan, Huitao; Guo, Haina; Zhong, Ling; Li, Zhuanfen; Zhou, Ping; et al. (Frontiers in Public Health, 2024)
Background: Persistent Human Papillomavirus (HPV) infection remains a key risk factor for cervical cancer. HPV-based primary screening is widely recommended in clinical guidelines, and further longitudinal studies are needed to optimize strategies for detecting high-grade cervical lesions compared to cytology.Methods: From November 2015 to December 2023, a total of 31,942 participants were included in the real-world observational study. Among those, 4,219 participants underwent at least two rounds of HPV tests, and 397 completed three. All were tested for high-risk types of HPV 16